Nucleic acid-based biosensors: analytical devices for prevention, diagnosis and treatment of diseases - Carvajal Barbosa, Laura; Insuasty Cepeda, Diego; León Torres, Andrés Felipe; Arias Cortes, Maria Mercedes; Rivera Monroy, Zuly Jenny; Garcia Castaneda, Javier Eduardo (Vitae, 2021)
BACKGROUND : Biosensing techniques have been the subject of exponentially increasing interest due to their performance advantages such as high selectivity and sensitivity, easy operation, low cost, short analysis time, simple sample preparation, and real-time detection. Biosensors have been developed by integrating the unique specificity of biological reactions and the high sensitivity of physical sensors. Therefore, there has been a broad scope of applications for biosensing techniques, and nowadays, they are ubiquitous in different areas of environmental, healthcare, and food safety. Biosensors have been used for environmental studies, detecting and quantifying pollutants in water, air, and soil. Biosensors also showed great potential for developing analytical tools with countless applications in diagnosing, preventing, and treating diseases, mainly by detecting biomarkers. Biosensors as a medical device can identify nucleic acids, proteins, peptides, metabolites, etc.; these analytes may be biomarkers associated with the disease status. Bacterial food contamination is considered a worldwide public health issue; biosensor-based analytical techniques can identify the presence or absence of pathogenic agents in food. OBJECTIVES: The present review aims to establish state-of-the-art, comprising the recent advances in the use of nucleic acid-based biosensors and their novel application for the detection of nucleic acids. Emphasis will be given to the performance characteristics, advantages, and challenges. Additionally, food safety applications of nucleic acid-based biosensors will be discussed. METHODS: Recent research articles related to nucleic acid-based biosensors, biosensors for detecting nucleic acids, biosensors and food safety, and biosensors in environmental monitoring were reviewed. Also, biosensing platforms associated with the clinical diagnosis and food industry were included. RESULTS: It is possible to appreciate that multiple applications of nucleic acid-based biosensors have been reported in the diagnosis, prevention, and treatment of diseases, as well as to identify foodborne pathogenic bacteria. The use of PNA and aptamers opens the possibility of developing new biometric tools with better analytical properties. CONCLUSIONS: Biosensors could be considered the most important tool for preventing, treating, and monitoring diseases that significantly impact human health. The aptamers have advantages as biorecognition elements due to the structural conformation, hybridization capacity, robustness, stability, and lower costs. It is necessary to implement biosensors in situ to identify analytes with high selectivity and lower detection limits.